Structural basis of lipopolysaccharide translocon assembly mediated by the small lipoprotein LptM - Ryoji Miyazaki; Mai Kimoto; Hidetaka Kohga; Tomoya Tsukazaki (Cell Reports, 2025)
Summary: Gram-negative bacteria possess an outer membrane (OM) that acts as a barrier against toxic compounds. Lipopolysaccharide (LPS) in the outer leaflet of the OM is crucial for barrier function and is transported to the OM by the LPS transport system. The LPS translocon (the LptDE complex), mediates LPS assembly into the OM. Recently, the small lipoprotein LptM was identified as an LptDE interactor that facilitates LptD maturation. However, its mechanism remains unclear. Here, we investigate the detailed interaction between LptM and LptD. We find that LptM interacts with the folded LptD intermediate at the late stage of its maturation. Mutational analyses demonstrate that the N-terminal conserved region of LptM is essential for its function. Cryoelectron microscopy structural analysis of the Escherichia coli LptDEM complex, combined with biochemical analyses, reveals the molecular basis of the LptM-LptD interaction and its functional importance. Thus, we propose that LptM stabilizes LptD for proper assembly.